PEMBUATAN APLIKASI PELAYANAN KEMOTERAPI RUMAH SAKITBERBASIS SMS GATEWAY - Sustin Ferlinda; Rinda Nurul Karimah; Eva Dwiana Putri (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Application Development Services chemotherapy is needed to accelerate and improve the discipline of patients in chemotherapy. Chemotherapy is the administration of anti-cancer drug that aims to kill cancer cells. Chemotherapy is a treatment that is sustainable therefore chemotherapy form to facilitate the recording clerk brought the further treatment, it causes a form of chemotherapy patients are often damaged or lost. Need information system services in the Hospital chemotherapy to chemotherapy patient care records electronically. The method used in this study is the waterfall, this type of research is qualitative research. Collecting data in this study using observation, interviews, documentation and brainstorming. Making the application of chemotherapy services using programming language Microsoft Visual FoxPro 9.0 which refers to a form of chemotherapy in the hospital. The results of this study are Sosftware product / service application of chemotherapy in the hospital consists of master data include: patient data, drug data, the data ICD10 and user data; transaction data includes: registration data, the data protocol doctor, nurse protocol data, assessment data in chemotherapy patients, records of drug administration and schedule of chemotherapy; the report includes: traffic reports, reports of drugs, chemotherapy schedule, report 10 illnesses and SMS is sent to the patient's Phone numbers reminded every jadwa control / chemotherapy reminder.